Clinical Biochemistry ; fundamentals of biomedical science - Ahmed, Nessar (Fundamentals of Biomedical Science., 2017)
'Clinical Biochemistry' places the theoretical foundations of clinical biochemistry firmly in a practical environment. Written for students with a grounding in fundamental biochemical concepts, it demonstrates how the biomedical scientist applies these principles to key laboratory investigations.--